Penegakan Hukum Terhadap Judi Online di Aceh Tenggara: Kendala dan Strategi Pemberantasan - Rif'at, Rif'at; Yazid, Imam (IAIN Langsa, 2025)
This study aims to analyze the law enforcement against online gambling players in Aceh Tenggara Regency, particularly in the implementation of Qanun Aceh Number 6 of 2014 concerning Jinayat Law. This research uses a case study approach with an empirical legal research method. Primary data is obtained through interviews and observations with law enforcement officers, offenders, and the public regarding online gambling, while secondary data is collected from document reviews, regulations, and related literature. The research findings indicate that law enforcement against online gambling offenders in Aceh Tenggara has been carried out by law enforcement agencies, but the results are still not optimal as online gambling practices continue to expand. The main challenges faced are the lack of public awareness, limited technological resources, and insufficient training and coordination among agencies, which require a more effective strategy to address these issues.